Konsumsi makanan tinggi natrium, kesukaan rasa asin, berat badan, dan tekanan darah pada anak sekolah - Heni Hendriyani; Enik Sulistyowati; Astidio Noviardhi (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2016)
Background: It is a fact that natrium consumption relates to hypertension and the risk of heart disease and stroke. Even though it is common happened in later life, hypertension can be started in early age.Objective: The aim of the study is to identify salty food preference, high natrium food consumption, natrium intake, weight and its correlation with blood pressure among schoolchildren.Method: The study used cross-sectional design. There were 151 samples from junior high school chosen by purposive sampling. Food salty level data was assessed by eating the snack with three different salt concentration. High and low natrium source food and natrium intake data were taken using semi-quantitative food frequency questionnaire. Blood pressure was measured by sphygmomanometer digital. Bivariate analysis was used Chi-square and Rank Spearman test.Results: The study revealed that 74,2% children prefer snack with the salt level above recommendation (> 0,5 gr salt per portion ). There were 22,5% children have natrium intake from food only ≥2000 mg (above recommendation). As much as 35,8% children fall into hypertension category based on their blood pressure (BP) level. There was a significant relationship between high natrium food consumption score with natrium intake (p=0,002). There were significant correlation between weight with systolic and diastolic BP ((p=0,000 r=-0,549 and p=0,000 r=-0,412). There were no correlation between atrium intake with systolic and diastolic BP (p=0,764; r= 0,0025 and p=0,819 r=0,19).Conclusion: Healthy food and maintaining normal weight information and education must be done for children as early as possible.